Efeito combinado de fitoterápicos anabolizantes e exercício resistido em camundongos machos e fêmeas submetidos à castração - Martins, Jerônimo Pietrobon (2020)
Herbal medicines have been widely used by the population, with the purpose of increasing muscle mass, weight loss, strength and general performance. These phytotherapics might have beneficial effects in clinical situations of hormonal reduction, such as in menopause and andropause. However, additional scientific investigations are still needed to prove the effectiveness of the natural products used for this purpose. In the present study, the effects of lyophilized extracts of Ajuga turkestanica, Euricoma longifolia, and Urtica dioica were investigated individually, in addition to the combination of the three plants (TLU), in castrated males and females (ORX and OVX, respectively) and non-castrated mice (SHAM). In addition, the use of extracts was evaluated, with and without the association with resistance exercise, which consisted of training to climb an inclined ladder, with the progressive addition of weights on the animal's tail. The contents of active compounds in the lyophilized extracts were confirmed by LC-UV and LC-MS, indicating that the extract of turkestanica contains 7.8% of phytosterols, with 0.501 mg/g of turkesterone. For E. longifolia extract, the phytosterol content was 0.5%, corresponding to 0.009 mg/g of euricomanone. Finally, for U. dioica, the phytosterol content was 2.8%, with 0.016 mg/g β-sitosterol. Regarding in vivo experiments, C57BL/6Junib mice of both sexes were submitted to castration surgery. After 8 weeks, resistance exercise protocol and supplementation with extracts were started, for additional 8 weeks. As outcomes, muscle mass, adiposity, grip strength, fatigue, general locomotor activity and biochemical and inflammatory parameters were evaluated. OVX animals showed increased body weight gain, accompanied by increased fatigue, which were reversed by exercise. The final weight of the OVX females was reduced by the combination of exercise and supplementation with U. dioica extract. Conversely, in ORX animals, a marked reduction in body weight was observed, accompanied by muscle atrophy and increased inguinal adipose tissue, without showing a reversal with exercise. However, the combination of resistance exercise, with extracts of E. longifolia or U. dioica, was able to reduce abdominal adiposity in ORX males. SHAM females, trained and treated with A. turkestanica extract, showed an increase in grip strength when compared to the sedentary control group. Interestingly, treatment with the same extract also increased grip strength in ORX males, with or without the combination with exercise. Intervention with exercise, combined with treatment with TLU, increased the resistance to fatigue in OVX females. In addition, E. longifolia and U. dioica extracts, as well as TLU, reduced the time required to complete the climb on the inclined ladder in ORX animals. In SHAM females and males, resistance training increased the travelled distance and speed, according to the evaluation in an open field apparatus. For OVX females, there was an increase in the travelled distance and speed, in the experimental groups trained and supplemented with A. turkestanica, U. dioica or TLU. In males, the combination of resistance exercise and supplementation with E. longifolia or U. dioica was effective in increasing both locomotor activity parameters. As for the total activity time, only SHAM males had an increase in this parameter, when submitted to resistance exercise and treatment with A. turkestanica. In the histological analysis, there were no significant differences in relation to the total area of muscle fibers or adipocytes, when all experimental groups were compared. There was a change in the frequency of distribution of muscle fibers in OVX females, trained and treated with E. longifolia extract, with an increase of fibers between 0 and 500 μm2. Alternatively, the frequency of fibers with 1500-2000 μm2 was reduced in sedentary OVX females, treated with turkestanica extract. The same was observed for trained OVX females, who received extracts of U. dioica or TLU. Finally, sedentary OVX females had an increase in fibers> 3000 μm2, after treatment with E. longifolia. In relation to males, there was an increase in fibers of smaller diameter (0 to 500 μm2) in ORX animals. SHAM males, trained and treated with E. longifolia extract, had a significant increase in fibers with 2500-3000 and> 3000 μm2. The evaluated biochemical and inflammatory parameters did not change with treatments and/or exercise. The exception was an increase in non-HDL cholesterol in OVX females, which was prevented by treatment with TLU, regardless of exercise. Discrete differences were observed in the weights of liver and kidneys, without any changes in brain or bone wet weights, in the different groups. In summary, the studied phytoanabolic extracts appear to modulate different parameters related to hormonal reduction, in males and females. Compared to isolated exercise, the association of these herbal medicines with resistance exercise seems to display better results, being an alternative to be explored for the management of diseases related to hormonal decline, such as sarcopenia.